The impact of Covid-19 pandemic on older people in Malaysia: A review - Khairul Hanim Pazim; Roslinah Mahmud; Beatrice Lim Fui Yee; Noor Fzlinda Fabeil; Juliana Langgat (Universiti Malaysia Sabah, 2021)
In Malaysia, the presence of more aggressive strains with higher infectivity impacted the decision to impose a state-wide comprehensive lockdown on June 1, 2021, in accordance with the third Movement Control Order (MCO 3.0). Based on COVID-19 mortality statistics, studies have found that the risk of severe illness with COVID-19 increases with age, with older adults and patients with comorbidities more likely to have a more severe course of disease and a higher chance of death than other age groups. The impact of COVID-19 on this vulnerable population is likely to be varied; disturbances in socioeconomic, health, sociocultural, and familial intergenerational support are predicted to be significant components impacted that are unique to Malaysia when compared to other countries. Furthermore, many older Malaysians may be dependent on their offspring for help, which could complicate matters even further, especially during a lockdown when visits are restricted. Finally, the growing importance of digital platform use among the elderly is a problem that needs to be addressed. The purpose of this article is to examine the impact of the COVID-19 on older people in the context of exploring their social and economic independence, emphasizing the importance of promoting effective supports and networks to ensure the well-being of these vulnerable older people during a pandemic.